Crop wild relatives of Karachay-Cherkessia: inventorying and conservation prospects - L. V. Bagmet (Труды по прикладной ботанике, генетике и селекции)
Studying wild relatives of cultivated plants in each specific region is an essential component in assessing the state of national plant genetic resources. This is especially true for the regions of the Russian Caucasus, with its tremendous diversity of plant species. This paper presents the results of exploring crop wild relatives (CWR) in natural plant communities of the Karachay-Cherkess Republic. The author conducted an inventory of CWR and analysis of their species composition in Karachay-Cherkessia. The CWR list includes 516 species belonging to 134 genera of 36 families; in this list, 449 species from 107 genera of 33 families are native to this region. The Dzheguta floristic district is the richest in CWR species diversity (391 species). There are 350 and 346 species in the Arkhyz and Uchkulan districts, respectively, and 301 species in the Cherkessk district. Species were ranked according to their agricultural value and economic importance: the 1st rank was assigned to 149 plant species, 2nd rank to 17, 3rd rank to 32, 4th rank to 97, and 5th rank to 222 species. In the context of their economic use, the species for feed (158) and food (136) purposes dominated over those for medicinal (60), melliferous (54), ornamental (53), industrial (51), and revegetation (5) applications. The list of priority conservation species was compiled for CWR of Karachay-Cherkessia according to the criteria of rarity and vulnerability, based on the analysis of the CWR species distribution over the studied area and their assessment for useful economic and biological traits. A map showing localities of these species within the Republic is presented, and recommendations are given for their effective conservation.